Democratic Values in Early Care of Children in A Children Garden - Ali, Musyafa; Prima, Ellen (Indonesian Journal of Early Childhood Education Studies, 2020)
Parents as the main caregivers play a very important role, because the parenting patterns will greatly affect the growth and development of children. Every parent hopes that their children can grow well according to the aspects of development and can grow optimally, so that later the children will become smart children. However, the busyness of the parents forced the parents to leave their children at the TPA. This is where TPA as a Children Gareden plays a very important role in the process of caring for a child. This research was conducted with the aim of knowing the results of the implementation of democratic parenting in early childhood. This study uses a qualitative descriptive field research method. The research location is in the RAPSI RANUPAKSI Children Gareden, Karangpucung, South Purwokerto, Banyumas Regency. The research subjects include teachers or caregivers and parents of children. Data obtained through observation, interviews, and documentation. The results of this study describe the implementation of democratic parenting patterns and democratic values ​​in parenting carried out by caregivers in early childhood in the RAPSI RANUPAKSI Children Gareden Karangpucung, South Purwokerto, Banyumas Regency, this research shows the process parenting activities, and democratic values ​​in the childcare process in the Children Gareden . Recommendations for future research as a material for research renewal can be done not only in childcare institutions but also parenting patterns carried out by families. So it can be known the connection, relationships, wider and profound impact related to the relationship of foster care institutions and parents or families.